Potential Functional Variants for Fatness, Carcass and Meat Quality Traits in Exon 3 of Fat Mass and Obesity-Associated Gene in Indonesian Ducks - Gunawan , Asep; Anggraeni; Listyarini, Kasita; Sumantri, Cece (International Journal of Poultry Science, 2018)
Background and Objective: The fat mass and obesity-associated gene (FTO) regulates glucose metabolism, body weight and fat content, it is also involved in DNA repair, fatty acid (FA) metabolism and post translational modification. Due to these functions, FTO may affect FAs, carcass and meat quality in ducks. The objective of this study was to identify functional variants of FTO associated with fatness, carcass and meat quality and to investigate the tissue expression profile of the FTO gene in ducks. Methodology: Fifty-seven Indonesian Cihateup ducks were used in this study. Tissues from breast muscle and liver were used to evaluate genomic DNA and mRNA expression. Fatness traits, which include FA composition, carcass and meat quality, were evaluated at 12 weeks. Results: A SNP in exon 3 of the SCD gene was significantly associated with breast muscle for carcass traits and lauric acid (C12:0) for FA composition, however, there was no significant association with meat quality traits. To measure the mRNA expression of FTO, ducks were divide into three genotypes (AA, AG and GG). Compared to the AG and GG genotype, the AA genotype ducks had greater breast muscle weight and higher lauric acid levels (C12:0) for carcass and FA traits, respectively. FTO mRNA expression was significantly higher in genotype AA and GG ducks. Conclusion: The SNP of FTO in exon 3 is a functional SNP that regulates carcass and FAs specific for breast muscle weight and lauric acid levels in ducks.